Fears of a Setting Sun : The Disillusionment of America's Founders - Rasmussen, Dennis C. (Dennis Carl), 1978- (Book collections on Project MUSE., 2021)
"Whatever sense of hope the Founder Fathers may have felt at the new government's birth, almost none of them carried that optimism to their graves. Franklin survived to see the Constitution in action for only a single year, but most of the founders who lived into the nineteenth century came to feel deep anxiety, disappointment, and even despair about the government and the nation that they had helped to create. Indeed, by the end of their lives many of the founders judged the Constitution that we now venerate to be an utter failure that was unlikely to last beyond their own generation. This book tells the story of their disillusionment. The book focuses principally on four of the preeminent figures of the period (1787): George Washington, Alexander Hamilton, John Adams, and Thomas Jefferson. These four lost their faith in the American experiment at different times and for different reasons, and each has his own unique story. As Rasmussen shows in a series of three chapters on each figure, Washington became disillusioned above all because of the rise of parties and partisanship, Hamilton because he felt that the federal government was not sufficiently vigorous or energetic, Adams because he believed that the American people lacked the requisite civic virtue for republican government, and Jefferson because of sectional divisions brought on (as he saw it) by Northern attempts to restrict slavery and consolidate power in the federal government. Washington, Hamilton, Adams, and Jefferson were the most prominent of the founders who grew disappointed in what America became, but they were certainly not the only ones. In a final chapter Rasmussen shows that most of the other leading founders-including figures such as Samuel Adams, John Jay, James Monroe, and Thomas Paine-fell in the same camp. The most notable founder who did not come to despair for his country was the one who outlived them all, James Madison. Madison did harbor some real worries but a final chapter also explores why Madison largely kept the republican faith when so many of his compatriots did not"--